Penerapan SAK EMKM dalam Penyusunan Laporan Keuangan UMKM di Kecamatan Sambikerep: (Studi Kasus pada UMKM Igulali) - Faizah Maulanda Salsabilla; Condro Widodo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
MSMEs have a significant role in the Indonesian economy. Ineffective finance management is simply one of the numerous challenges that MSME owners encounter. SAK EMKM anticipates MSME players being able to compile and submit financial reports. The goal of this project is to improve MSME actors' comprehension and capacity to generate organized and standardized financial reports. This study employs a descriptive methodology in conjunction with a qualitative approach. The data were gathered mostly through interviews and direct observation of Igulali MSME participants in Jelidro Indah II No. 06, Sambikerep District, Surabaya City. According to the research findings, MSMEs preserve basic records, such as entering and exiting monies. This is due to their lack of awareness of how to compile financial accounts in line with SAK EMKM, which causes them to just document income in general rather than going into further depth.